Microsoft System Center 2016 Orchestrator Cookbook - Second Edition - Seidl, Michael (Packt Publishing Limited, 2017)
bOver 30 recipes to automate your mission-critical tasks using the new and powerful Microsoft System Center 2016 Orchestrator/bh2About This Book/h2ulliCreate powerful runbooks for the entire System Center 2016 product line/liliExplore System Center 2016 Orchestrator to manage and automate your datacenter/liliA recipe-based guide to using SCO efficiently/li/ulh2Who This Book Is For/h2If you are a system administrator and want to simplify the process of automating system administration tasks using System Center Orchestrator 2016 then this book is for you.